""Paradise Lost"" and the Rhetoric of Literary Forms - Lewalski, Barbara Kiefer (Princeton : Princeton University Press, 2014)
This comprehensive study interprets Paradise Lost as a rhetoric of literary forms, by attending to the broad spectrum of literary genres, modes, and exemplary works Milton incorporates within that poem. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton.
Description based upon print version of record.
Cover
Keywords: Literary form -- History -- 17th century; Milton, John, 1608-1674. Paradise lost; Milton, John, -- 1608-1674.; Literary form -- History -- 17th century; POETRY / English, Irish, Scottish, Welsh; Electronic books